THE INTEGRATION OF THE MARKET PARTICIPANTS — THE BASIS OF COMPETITIVENESS IN A HIGHLY DYNAMIC EXTERNAL ENVIRONMENT - T.S. Shcherbakova (Krymskij Naučnyj Vestnik, 2017)
The article analyzes approaches to improve the competitiveness of business entities through the establishment of alliances and associations within which cooperation is conducted on the principles of co-creation and co-creation. This principle the author considers as the basis of ensuring the qualitative development of enterprises in conditions of high dynamics of the environment.